2016
DOI: 10.1177/1359105316664127
|View full text |Cite
|
Sign up to set email alerts
|

Association between change in self-efficacy to resist drinking and drinking behaviors among an HIV-infected sample: Results from a large randomized controlled trial

Abstract: Heavy drinking among HIV-infected individuals is associated with health complications. Health-behavior self-efficacy may be characteristically low among this population, or negatively affected by HIV-infected status. We assessed whether self-efficacy to resist drinking increased during brief educational and motivational drinking-reduction interventions within HIV primary care, and whether increases in self-efficacy predicted drinking among HIV-infected heavy-drinkers. Results indicate that increases in self-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…"ml" is milliliter earlier research done in other countries, which showed approximately 25% used alcohol in Africa and 21.8% in the United States in previous month [16,17]. Evidence has shown that the health outcomes are worse in patients who often drink alcohol, including a higher incidence of psychosocial problems and lower treatment adherence levels [18][19][20][21][22]. In addition, most of these drinkers were male PLWHA, which was consistent with findings from other studies [23][24][25].…”
Section: Discussionsupporting
confidence: 86%
“…"ml" is milliliter earlier research done in other countries, which showed approximately 25% used alcohol in Africa and 21.8% in the United States in previous month [16,17]. Evidence has shown that the health outcomes are worse in patients who often drink alcohol, including a higher incidence of psychosocial problems and lower treatment adherence levels [18][19][20][21][22]. In addition, most of these drinkers were male PLWHA, which was consistent with findings from other studies [23][24][25].…”
Section: Discussionsupporting
confidence: 86%
“…In a VA study of 2101 PLWH, Williams and colleagues (2017a) reported that 77% of patients with unhealthy alcohol use had alcohol brief interventions, but this did not result in reductions in alcohol use over time. Other recent research shows promise (Chander et al, 2015;Gause et al, 2018), including our randomized clinical trial (Satre et al, 2019) in KPNC demonstrating that motivational interviewing can improve drinking outcomes for PLWH in HIV primary care with low motivation at baseline to change drinking habits. Despite the reduced likelihood of alcohol brief interventions, it should be noted that PLWH were more likely to have an addiction specialty care visit during follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Greater alcohol use has also been shown to track closely with adverse changes in the VACS index score, a composite HIV severity, and prognostic score (Williams et al, 2019). To avoid adverse consequences of unhealthy alcohol use, health systems are increasingly implementing routine screening and treatment (Bradley et al, 2006; Mertens et al, 2015), although studies evaluating the effectiveness of alcohol interventions among PLWH have mixed results (Chander et al, 2015; Gause et al, 2018; Samet and Walley, 2010; Satre et al, 2019; Williams et al, 2017a).…”
mentioning
confidence: 99%
“…HealthCall's mechanisms of change are hypothesized to include the following: (1) increased awareness of the target behavior through self-monitoring; (2) improved accuracy about change through personalized feedback; (3) goal setting and attainment; (4) increased participant commitment to change (Aharonovich, Stohl, Ellis, Amrhein, & Hasin, 2014), and (5) improved self-efficacy (Gause et al, 2016). HealthCall-S satisfaction ratings and end of treatment debriefing indicated that participants positively endorsed these components.…”
Section: Discussionmentioning
confidence: 99%